INTERNATIONAL INVESTMENT COOPERATION AND ITS ROLE IN THE POST-WAR RECONSTRUCTION OF THE COASTAL AREAS OF UKRAINE - BIELIAK, Illia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the study of the scientific and theoretical foundations of international investment cooperation and the analysis of its impact on the economic development of the coastal areas of Ukraine. It is conducted the critical review of existing definitions of the studied concept. It is proposed the proper definition that considers the socio-economic nature of such cooperation. International investment cooperation should be understood as economic relations formed as a result of international investment and mediating the movement of international investments. It is defined the main purpose of the investigated phenomenon, which consists in making a profit. It is emphasized  the key difference between international investment cooperation and other forms of cross-border movement of capital by the presence of a commercial basis that accompanies this process in one way or another. It is considered previous developments in formulating the principles of investment cooperation. It is proposed own list of principles for its implementation: economic expediency, freedom and equality of parties, fair distribution of benefits and risks, regulatory and tax coordination, social, environmental and ethical responsibility, strategic, transparent and contractual nature.By constructing polynomial regression equations of the dependence of the gross product of the coastal regions of Ukraine on direct foreign investment, the regularities of the influence of international investment cooperation on the economic development of the respective territories are investigated. It is determined that such cooperation is characterized by its fundamental importance for the economic growth, its direct impact on the regional economic complex, the marginal possibilities of rational placement of international investments and the unevenness of the positive effect they generate. It is substantiated the practical advantages and limitations of the potential increase in the volume of international investment in the post-war period.
Keywords: international investment cooperation; coastal areas; post-war recovery; direct foreign investment; international movement of capital